Heart rate variability is more sensitive to stress than heart rate in specialist police undergoing selection. - Colin Tomes; Ben Schram; Elisa Canetti; Robin Orr (PLoS ONE)
Police tactical group (PTG) officers respond to the most demanding and high-risk police situations. As such, PTG personnel require exceptional physical fitness, and selection for employment often evaluates fitness both directly and indirectly. While heart rate (HR) is often used to measure physical effort, heart rate variability (HRV) may be a valuable tool for measuring stress holistically. The primary aim of this research was to investigate whether HRV was more sensitive than HR at monitoring workload during key PTG selection activities. As aerobic fitness is associated with workload during these tasks, a secondary aim was to investigate relationships between HRV, HR and aerobic fitness during the same tasks. The relationships between HRV (percentage of adjacent R-R intervals varying by 50% or more; pRR50%) and HR, as measured by ambulatory electrocardiograms obtained during a specialist police selection course, as well as aerobic fitness, as determined via total shuttles completed on the 20-meter multistage fitness test (MSFT; 'beep test'), were investigated. This study included a cohort of six male PTG candidates (n = 6) undergoing selection. As illustrated by a time-series plot, HR values were generally unremarkable, but HRV values were potentially depressed, and tentatively indicated overstress when count data from consecutive short-term analyses were derived. The MSFT was significantly, positively, correlated with pRR50% (ρ (6) = 0.812, p = 0.050, Fisher's z = 1.132). The MSFT and nonlinear HRV, frequency domain HRV, and HR were not significantly correlated. When assessed by linear regression, neither HRV nor HR were predicted by MSFT score. These findings indicate that HR alone is likely not sufficiently sensitive to provide detail on the stress response of candidates undertaking essential tactical tasks that combine physical stressors with cognitive load in adverse conditions. HRV analysis may provide additional insights regarding candidate suitability, particularly during dynamic and multifaceted assessments, though the causal direction of the relationship between HRV and aerobic fitness remains unclear.